Influência do semestre letivo e estresse na qualidade do sono de alunos do curso de ciências biológicas da FEIS/UNESP - Oliveira, Leticia Urani Domingues de [UNESP]; [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Purpose: The objective of this study was to analyze the sleep quality of undergraduate students in Biological Sciences at UNESP in Ilha Solteira, in order to assess whether the academic semester and the performance of assessment activities alter the sleep quality of students. Methods: 64 Biological Sciences students at FEIS/UNESP, 18 from the 1st semester and 46 from the 9th semester; this second group, divided into students in periods with and without evaluative stress, answered questionnaires for self-assessment of sleep quality for 7 days. Data were analyzed using RStudio statistical software, version 1.1.442. Subsequently, the Shapiro-Wilk test was performed to verify the normality of the variables, for parametric data, the Student's T test was applied, and for non- parametric data, the Wilcoxon Rank Sum Test was applied. Results and conclusion: The quality of sleep was considerably depleted in the comparison between freshman and senior students, notably by the decrease in sleep hours and worse self-assessment of the sensation upon waking up. Additionally, physical activity, which is quite rare in veterans, may be a factor in improving sleep quality, and should be encouraged during such school period. Regarding the assessment of stress from evaluative activities, it was noted that the parameters related to the sensation when waking up and the duration of sleep worsened in students during the evaluation period.

Proposta: O objetivo deste trabalho foi analisar a qualidade de sono de alunos de graduação em Ciências Biológicas da UNESP de Ilha Solteira, com vistas a avaliar se o semestre letivo e a realização de atividades avaliativas alteram a qualidade de sono dos discentes. Métodos: 64 alunos regularmente matriculados no curso de Ciências Biológicas da FEIS/UNESP, 18 do 1º semestre e 46 do 9º semestre; este segundo grupo subdividido em alunos em período com e sem estresse avaliativos, responderam durante 7 dias questionários de autoavaliação da qualidade de sono. Os dados foram analisados utilizando o software estatístico RStudio, versão 1.1.442. Posteriormente, realizou-se o teste de Shapiro-Wilk para verificar a normalidade das variáveis, para os dados paramétricos foi aplicado o teste T de student, e não paramétricos foi aplicado o Teste de soma de Postos de Wilcoxon. Resultados e conclusão: A qualidade de sono foi depletada consideravelmente na comparação entre alunos calouros e veteranos, notadamente pela diminuição de horas de sono e pior autoavaliação da sensação ao acordar. Adicionalmente, a realização de atividades físicas, bastante rara em veteranos pode ser um fator para a melhora na qualidade de sono, e deve ser estimulada em tal período letivo. Quanto à avaliação do estresse proveniente de atividades avaliativas notou-se que os parâmetros ligados à sensação ao acordar e à duração do sono pioraram em alunos durante o período avaliativo.
Influence of the school semester and stress on sleep quality of students of the biological sciences at FEIS/UNESP
Keywords: Sleep quality; Biological sciences; Evaluative activities; Stress; Qualidade do sono; Ciências biológicas; Atividades avaliativas; Estresse